Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

DSAP-WeedNet: A Down-Scale Attention-Guided Lightweight Network for Real-Time Weed Detection Enabling Precision Control in Potato Fields - Lei Han; Yi-Teng Wu; Ke-Jun Fan; Rui-Feng Wang; Wen-Hao Su (Potato Research, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Experimental and numerical study of diaphragm in-plane stiffness on the seismic performance of building structures with DCPCF - Yuan-yuan Sun; Rui Pang; Shu-ting Liang; Yi-ming Wen; Chun-lin Wang (Engineering Structures, 2026)

Spatiotemporally energy-managed phase-change evaporators for continuous solar desalination - Qian Chen; Xingdong Qiu; Rui Yang; Jinchi Li; Jun Xia; Hongbing Wang; Lihong Zhou; Yi Lu; Size Zheng; Mingming Zheng; Xiaoke Li (Chemical Engineering Journal, 2026)

Ultrafast underwater self-sustaining manufacturing of polymer concrete driven by frontal polymerization - Jiongfeng Sun; Shicheng Ding; Rui Wang; Yi Hong; Guofu Qiao (Chemical Engineering Journal, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Development of a bifunctional dynamic control system for effective product synthesis in Bacillus licheniformis DW2 - Yi Rao; Jiaqi Wang; Junyan Liu; Rui Zhao; Xin Ma; Dongbo Cai; Shouwen Chen (Bioresource Technology, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Using spherical protrusions for simultaneous pressure pulsation mitigation and efficiency enhancement in a giant Francis turbine across a wide load operation - Lei Tang; Xiao-Wen Huang; Rui Zhao; Tian-Yi Shi; Wen-Quan Wang (Ocean Engineering, 2026)

White mica as an exploration vector for Archean gold deposits: Integration of in-situ chemistry and SWIR spectroscopy at Kanowna Belle and Sunrise Dam, Western Australia - Yi-Hao Liu; Rui Wang; Dan-Ya Zhou; Yun Zhao (Journal of Geochemical Exploration, 2026)

Climate and soil shape Daqu wheat quality and seed microbiome via rhizosphere taxa and microbial assembly - Kangjie Yu; Shuanghui Wang; Hanrui Shi; Rui Luo; Zijian Chen; Yi Xia; Qingdong Zeng; Yi Ma; Dejun Han (Food Research International, 2026)

Differential regulation of exercise fatigue by Spirulina peptides: energy metabolism and antioxidant defense mechanisms mediated in a comparative swimming model - Tao Ding; Zhaoxin Li; Rui Duan; Junjie Zhang; Lihong Xing; Xiaojie Sun; Fang Zhang; Qingyan Wang; Shuo Qie; Yi Yang; Cuiping Song (Food Chemistry, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Rainfall reshapes intra-urban activity patterns: Multi-level insights from human mobility in China - Nan Wang; Yunyan Du; Jiawei Yi; Wenna Tu; Sheng Huang; Peixian Luo; Xiaoyue Wang; Dingchen Hu; Rui Xu; Fuyuan Liang (Computers, Environment and Urban Systems, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Asymmetric and spatially heterogeneous urban sensitivity to inter-day temperature variability: Evidence from geo-tagged social media - Rui Xu; Jiawei Yi; Yunyan Du; Sheng Huang; Nan Wang; Jiale Qian; Dingchen Hu (Applied Geography, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Bone biochar as a bifunctional catalyst for sustainable co-removal of nitrate and phosphate in constructed wetlands - Tao Liu; Hao Qin; Sihan Li; Gongliang Zhang; Rui Wang; Yi Sun; Haihua Wu; Yuxin Zeng; Yi Chen (Water Research, 2026)

Synergistic integration of in situ generated Fe-S species and organohalide-respiring bacteria for complete dechlorination of carbon tetrachloride in groundwater - Boyu Jia; Rui Shen; Zhongdan Li; Yijun Mo; Yi Yang; Shanquan Wang (Water Research, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

A novel multiple imputation approach with recursive feature elimination BiLSTM for spatiotemporally seamless Landsat NDVI reconstruction - Guodong Zhang; Gaofei Yin; Yimin Ni; Yi Zhang; Rui Chen; Meilian Wang; Aleixandre Verger (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Diversity and drivers of marine heatwaves in the Beibu Gulf of the South China Sea - Bo Zhang; Qiang Wang; Lili Zeng; Kunshan Li; Yi Xie; Rui Shi (Climate Dynamics, 2026)

Retraction notice to “Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period” [Sci. Total Environ. 906 (2024) 167622] - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

Transcriptomic insights into the antifungal efficacy of Bacillus velezensis-synthesized silver nanoparticles against toxigenic fusarium verticillioides - Shumila Ishfaq; Xiaotong Gai; Xiaoyan Liang; Yi Ding; Rui Wang; Arslan Anjum; Yongzhan Cai; Amna Rafiq; Wei Guo (Pesticide Biochemistry and Physiology, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Dynamic sulfidation process of nanoscale zero-valent iron induced by sulfate-reducing bacteria and its effect on the reductive dechlorination of trichloroethylene - Shaoyu Wan; Lijuan Zhang; Siqi Zhuang; Yi Su; Qi Liang; Rui Shen; Shanquan Wang; Andrei Ivanets; Bekchanov Davronbek; Xintai Su (Environmental Research, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Sedimentary DOM composition governs the environmental mobility of palladium in tropical island estuaries - Zhixin Li; Yuyan Liu; Ling Wang; Hongwei Yi; Rui Xu; Jianan Liu; Haofeng Liu; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Unveiling the participation of microbiomes in the trait formation of economically important Pyropia haitanensis varieties - Yi Liu; Jingyi Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Lithium Enhances Survival Bias Associated with the Lateral Habenula Suppression - Kunlin Liu; Rui Zhu; Haoyue Guo; Jinghuan Li; Qianfu Wang; Yi He; Chenggang Zhu; Zheng Ma; Xiaodan Jiang; Jack van Honk; Jin Bao (Neuroscience Bulletin, 2026)

Structure, assembly, and biological assessment of microbial communities based on eDNA metabarcoding in the continuous river-estuary-sea system of the Yellow River Estuary, China - Gang Xie; Xiaoxia Yu; Ning Zhang; Jie Li; Rui Wang; Yu Wang; Xinlei Li; Dan Li; Wanting Wang; Shilong Ren; Yi Zhu; Guoqiang Wang (Marine Pollution Bulletin, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Techno-economic assessment of offshore wind multi-path energy conversion and storage-transport: electricity, hydrogen, and methanol - Lei Pan; Yunfei Ding; Yuxuan Wang; Yi Pang; Jianwei Chen; Yanwei Jing; Haibo Qiu; Rui Gao; Liyang Zhang (Ocean Engineering, 2026)

Domestic and exotic freshwater fish communities of different water systems under anthropogenic pressures: Diversity patterns, environmental drivers and ecological interactions - Peixuan Wang; Nan Yang; Xiaodong Hu; Lihua Niu; Jixiong Xu; Rui Huang; Li Lin; Yi Li (Journal of Environmental Sciences, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Germination-tunable structural remodeling of LAB-fermented soymilk gels: Unraveling gastrointestinal digestive fate and bioactive peptide release - Yaqiong Wang; Yi Wang; Zhijie Yao; Xin Rui; Pei Wang; Chong Xie; Runqiang Yang (Food Chemistry, 2026)

Fermentation properties and functional genes in Lactiplantibacillus plantarum based on complete genomes - Malina Kuerman; Rui Wang; Bayiyani Tuerxunhali; Huaxi Yi; Lanwei Zhang; Tongjie Liu (Food Bioscience, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

Rhizosphere microbial carbon utilization stimulates soil phosphorus fraction transformation in response to maize (Zea mays L.) and soybean (Glycine max.) interspecific interactions - Ruixue Wang; Lizhen Su; Dingjin Li; Zikun Yang; Rui Feng; Yi Zheng; Li Tang (Plant and Soil, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Synthesis, anticancer activity and molecular docking study of triphenylphosphonium-linked derivatives of oleanolic acid - Deshang Li; Bo Wang; Rui Wang; Jianjun Huang; Ruofan Chen; Yi Li; Na Wang; Qianqian Wang; Chenmeng Xu; Wim Dehaen; Qiyong Huai (Natural Product Research, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Partial sympatry of two interspersed Uroteuthis edulis (Loliginidae) clades reveals cryptic stock structure in the southern Taiwan Strait - Rui-Yi Hong; Lorenzo C. Halasan; Ke-Yang Chang; Chia-Hui Wang; Hsiu-Chin Lin (Fisheries Research, 2026)

Valorization of industrial carbide slag via microwave processing: A low-cost route to high-performance CaO-based CO2 sorbents - Fang Wang; Yi Dong; Shaojun Luo; Zixia Tian; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Futing Xia; Jiayu Feng; Lijuan Jia (Journal of Environmental Management, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Simultaneous removal of sulfamerazine and nutrients in wastewater by alternate coupling of photocatalysis and microalgal system: From system construction to multi-interactions and purification effects - Lin-Lan Zhuang; Rui Li; Xiao-Xiong Wang; Yuxin Wu; Yanhui Zhao; Xiaojia Yi; Hongyang Liang; Weiyi Qian; Jian Zhang (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Cortical Contributions to Local and Global Biological Motion Perception: Insights from Transcranial Magnetic Stimulation - Lianzi Xing; Zhongju Sun; Yushu Wang; Yiru Bao; Peng Cai; Rui Wang; Yi Jiang (Neuroscience Bulletin, 2026)

A Novel Approach for Estimating Peak-Strength Storage Strain Energy in Rockburst Proneness - Fengyun Wang; Rui Pan; Guojun Cai; Yi Cai; Kun Huang; Jian Lin (Rock Mechanics and Rock Engineering, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Integrated metabolomics and transcriptomics analyses provide insights into flavor and color regulation during tomato postharvest ripening - Xian-Kang Xiao; Wei-Xin Liu; Xiao Lu; Cai-Rui Chen; Xin-Yi Zhang; Xiao-Jun Pu; Feng Wang (Postharvest Biology and Technology, 2026)

Low-alkali activated Ca2+-KNBC/SA aerogel from waste citrus peel: Efficient and selective removal of Cu(II) and Cd(II) in acidic wastewater - Jiajia Yang; Rui Zhang; Ying Lei; Jian Yang; Maiming Ye; Zhengyu Luo; Hailing Li; Xiaofeng Zhou; Yi Huang; Xinyu Wang; Peng He (Journal of Environmental Management, 2026)

Critical thresholds in urbanization-vegetation dynamics: Multiscale remote sensing evidence from Chinese cities - Yining Shen; Nan Wang; Yunyan Du; Jiawei Yi; Sheng Huang; Wenna Tu; Peixian Luo; Rui Xu; Dingchen Hu (Journal of Environmental Management, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Integrated plastic film and straw mulching enhances potato tuber yield in mountainous regions by optimizing rhizospheric metabolites and root–microbe interactions - Kang Du; Xinyue Yang; Zhenpeng Deng; Xi Lin; Mengyuan Hu; Rui Jiang; Guolian Zheng; Xiaoping Yi; Xun Liu; Changwen Lyu; Jichun Wang (Field Crops Research, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Dynamic electric field modulation via BaTiO3-based staggered-type heterojunction for all-solid-state lithium-sulfur batteries - Yancheng Yang; Sizhe Wang; Fei Liang; Haizhou Zhao; Yi Gu; Rujing Liu; Jian Sun; Yao Yao; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Inhibiting NAT10 suppresses hepatocellular carcinoma progression by reducing Nrf2 mRNA stability and increasing oxidative stress - Wei Gu; Ziyi Ren; Jie Gao; Ziyi Shen; Yuanhui Wang; Luanqi Xu; Rui Qian; Qinyi Miao; Yifan Wu; Xiaomeng Hu; Yan Wu; Wei Liu; et al. (Chemico-Biological Interactions, 2026)

Responses of soil microbial communities in a large vanadium-titanium magnetite tailing dam under half a century of revegetation - Xiaofeng Zhou; Jiajia Yang; Ying Lei; Rui Zhang; Shuming Peng; Sihong Li; Yi Huang; Xinyu Wang; Peicong Zhang; Peng He (Plant and Soil, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Tracking the fate of organophosphate esters: from occurrence to risk in the lower Yangtze River water - Yi Zhou; Wenxuan Ma; Wanyu Li; Ge Yin; Jiajun Chang; Yao Xiao; Zhiliang Zhu; Rui Wang; Yanling Qiu (Environmental Science and Pollution Research, 2026)

Reduction of regulatory B cells is associated with high-risk clinical stratification in antiphospholipid syndrome patients - Rui Ma; You-yang Wang; Jing-hong Feng; Wen-yi Li; Yan Long (Immunologic Research, 2026)

Design, synthesis and antitumor activity of triphenylphosphonium-linked derivatives of quinazolinone - Qianqian Wang; Ruofan Chen; Rui Wang; Jianjun Huang; Yinuo Xu; Na Wang; Deshang Li; Chenmeng Xu; Bo Wang; Yi Li; Wim Dehaen; Qiyong Huai (Natural Product Research, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Gliadin hydrolysate-chitosan bilayer nanoparticles for berberine delivery: Controlled release, enhanced antioxidant activity, and lipid digestion regulation - Xiaoxiao Li; Yi Zhao; Aimei Liao; Yinchen Hou; Xinrui Zhang; Hailong Tian; Luyang Wang; Jin Liu; Jinyang Zhang; Jihong Huang; Rui Tan (Food Chemistry, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Kinetic and spectroscopic studies on the inhibitory mechanisms of deoiled egg yolk hydrolysate against pancreatic lipase - Lin Zhang; Rui Cui; Wei Liu; Shasha Wang; Yifang Yan; Yi Wang; Xi Huang (Food Bioscience, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Nanozyme-catalytic colorimetric microfluidic paper-based analytical device for rapid detection of miRNA-21 - Ke Shi; Rui Yi; Mengxi Yin; Xiaoli Wang; Yuting Zhang; Nandi Zhou (Systems Microbiology and Biomanufacturing, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

PINK1 deacetylation by emodin-induced SIRT3 upregulation alleviates acute kidney injury by Inhibition of ferroptosis - Rui Wang; Ziwei Zou; Yi An; Liulin Wang; Chengyin Li; Yinshui Zou; Guangzhi Wang (Inflammation Research, 2026)

Noise Characteristics and Shallow Subsurface Structure Detection in Coastal Zones: A Case Study from Dong’ao Island, Zhuhai - Siqing Liu; Sixu Han; Yongzhi Liang; Shuji Yang; Yi Chai; Tongying Hu; Ruifeng Wu; Yu Li; Qingxian Zhao; Zengjia Li; Wei Zhang; Xianqing Wang; et al. (Journal of Marine Science and Engineering, 2026)
Shallow subsurface structure detection in coastal zones serves as a critical foundation for resource development and engineering construction. However, conventional geophysical methods exhibit significant limitations in land–sea transition zones, where pronounced “boundary effects” create substantial “exploration gaps” due to difficulties in merging terrestrial and marine datasets. To achieve truly seamless subsurface imaging across the coastal boundary, this study develops and implements an integrated cross-boundary survey approach utilizing nodal seismometers and seismic ambient noise. At Dong’ao Island, Zhuhai, we deployed a comprehensive seismic profile spanning hillside, sandbeach, and seafloor environments to evaluate the method’s applicability in complex coastal settings systematically. Results demonstrate substantially stronger ambient noise energy in submarine environments compared to terrestrial settings. All stations recorded abundant and stable high-frequency (>1 Hz) noise signals, which are adequate for shallow subsurface imaging. Rayleigh wave dispersion curves extracted via the advanced Frequency-Bessel transform method enabled inversion of a continuous 2D shear-wave velocity profile along the survey line. Bedrock interface depths determined using the Horizontal-to-Vertical Spectral Ratio (HVSR) method showed remarkable consistency with the bedrock morphology revealed by the shear-wave velocity structure, validating the reliability of our approach in coastal environments. This research successfully demonstrates the feasibility of seismic ambient noise imaging as a bridging technique for land–sea exploration, providing an efficient, environmentally friendly, and continuous technical solution to overcome coastal zone exploration challenges.

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Developmental nonylphenol exposure triggers GPER‑dependent microglial activation and subsequent neuronal injury - Dianqi Yao; Siyu Yan; Rui Ding; Bingcheng Cai; Siyao Li; Yuanyuan Xu; Yi Wang (Journal of Hazardous Materials, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

System dynamics–based framework for modeling and assessing smart city resilience: a case study of Chengdu, China - Rui Li; Kum Fai Yuen; Yuhang Wang; Yi Lu (Sustainable Cities and Society, 2026)

Assessing pollutant leaching and migration from underground coal gasification residual coke - Yi Cheng; Caifang Wu; Rui Yang; Fangfang Wang; Xiuming Jiang; Shuai Xu (Process Safety and Environmental Protection, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Revealing the operando ORR mechanism of single-atom catalysts anchored in nanobowl structures for advanced hydroxide exchange membrane fuel cells - Sun-Tang Chang; Hui-Xin Liu; Yi-Ching Chu; Ying-Rui Lu; Chen-Hao Wang (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Injectable glucose-responsive hydrogels with hemorrhage control and microenvironmental regulation for diabetic wound repair - Zhengyuan Liu; Zhongyang Liu; Yi Yu; Xuechen Zhang; Fangyuan Yu; Rui Song; Xing Wang (Carbohydrate Polymers, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Additive effects of Lp(a) and inflammation on cardiovascular risk beyond LDL-C lowering: circulating and genetic evidence from 401,548 adults - Rui Li; Wenyue Dong; Wenxiu Wang; Youling Duan; Miao Zhang; Tao Huang; Xinwei Hua; Yi-Da Tang (Science Bulletin, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Effects of sun drying combined with baking processes on the flavor quality of Chongqing Tuocha raw tea - Hongyu Luo; Rui Chang; Shanmin Chen; Yueyun Liu; Yi Wang; Linying Yuan; Juan Yang; Ying Zhang; Ruiqi Duan; Quan Wu; Yingfu Zhong (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Local electron structure regulation inhibits Jahn-Teller effect of Ni/Fe/Mn-based oxide cathode toward wide-temperature sodium-ion batteries - Yuhang Zhang; Shihao Li; Rui Jin; Fangyan Liu; Yi Zhang; Huiru Wang; Ziyue Qiu; Zhian Zhang (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Typology-driven framework for revitalizing urban leftover spaces: Systematic review of practices and future research directions - Rui Qiao; Yi Sun; Siqiang Wang; Bo Lan; Chun Yin Chung (Land Use Policy, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Multi-omics investigation unveils the role of Eurotium cristatum fermentation in potentiating thinned young apple pomace for colitis-induced liver disorders amelioration - Jiayao Lv; Yi Wang; Lanqi Zhou; Shiyi Zhang; Wei Song; Rui Dong; Tianqi Liu; Guoze Wang; Lin Shi (Food Research International, 2025)

Qualitative and quantitative detection of Zn2+ in food: design, synthesis and characterization of a near-infrared probe with large Stokes shift - Shizhen Wang; Xin Wang; Wenhui Xue; Yi Huo; Mengyu Chen; Cuibing Bai; Qixiang Song; Chenxu Liu; Lin Zhang; Changqing Qu; Hui Miao; Rui Qiao (Food Chemistry, 2025)

Unraveling long-term health dynamics of impounded lakes integrating water diversion-adapted planktonic index of biotic integrity and machine learning - Xing Hou; Dawei Wang; Xiaodong Hu; Yi Li; Huanjun Zhang; Lihua Niu; Rui Huang; Jixiong Xu (Environmental Research, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Environmentally friendly, lightweight, and recyclable nanocomposite foams for sustainable electromagnetic interference shielding via integrating a dynamically crosslinked biobased polyamide system with supercritical carbon dioxide foaming - Chia-Hsing Lin; Chia-Wei Lee; Lyu-Ying Wang; Rui-Hao Li; Yi-Huan Lee (Chemical Engineering Journal, 2025)

Ternary eutectic solvents facilitate the production of well-dispersed chitin-glucan nanofibrils from shiitake mushrooms - Rui Zhou; Xingyu Yi; Yi Qin; Ruoyun Wu; Yang Wang; Liang Liu; Yimin Fan (Carbohydrate Polymers, 2025)

Novel laser-driven fast pyrolysis of biomass: Insights into biochar characteristics and applications - Rui Ma; Jintao Luo; Xiaoning Duan; Yuwan Sheng; Shaohui Wang; Deli Zhang; Fang Wang; Shuo Yang; Weiming Yi (Bioresource Technology, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

The multi-omics approach reveals the impact of Temnocephala digitata infection on Macrobrachium rosenbergii - Lianggang Wang; Yan Yang; Libin Huang; Guanghua Huang; Lan Zeng; Xiaohua Lu; Zhide Ruan; Shaokui Yi; Quanxin Gao; Tianhe Lu; Jingkai Qin; Liuchun Lan; et al. (Aquaculture, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Orally administered milk-derived extracellular vesicles alleviate hepatic metabolic dysfunction by targeting hepatocytes and modulating ER stress - Rui Zhang; Haoran Wang; Guoyue Wei; Xipeng Sun; Yifan Zou; Chaoting Wen; Tao Li; Huaxi Yi; Lingjun Tong (Chemical Engineering Journal, 2025)

Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Zhaocheng Liu; Rui Zhang; Yi Zhang; Huijun Mu; Xinyi Jiang; Jian Zou; Tingting Wang; Ying Yin (Chemical Engineering Journal, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

New point mutations in osmosensing two-component histidine kinase gene associated with iprodione resistance in Monilinia fructicola field isolates from China - Qian Long; Yiyi Guo; Miaomiao Yi; Changsheng Lu; Rui Zhong; Hao Zhang; Usama Amin; Dufang Ke; Zongwen Wang; Fengping Chen (Pesticide Biochemistry and Physiology, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Carrier-free methylene blue nanomedicine for prolonged hepatic visualization in anatomical hepatectomy: A translational study from bench to bedside - Hu Chen; Minglei Teng; Qihui Hu; Xiaoliu Liang; Hui Liu; Zhenjie Li; Xing Gao; Yisheng Peng; Xiaoyong Wang; Syed Faheem Askari Rizvi; Yi Lv; Hongwei Cheng; et al. (Chemical Engineering Journal, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Root-soil-microbe interactions mediate phosphorus and iron uptake from lithium iron phosphate nanomaterials - Yaqi Jiang; Yi Sun; Changcheng An; Pingfan Zhou; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Applied Soil Ecology, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Application and identification of monoclonal antibody targeting a novel epitope on p72 protein of African swine fever virus - Yu Dai; Xin Deng; Qi Wang; Ke Yang; Shuqing Yang; Xinran Li; Xinlei Liu; Yuanyuan Yang; Yu Gu; Yi Zheng; Rui Wu (Veterinary Microbiology, 2025)

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

Physics-encoded deep learning for integrated modeling of watershed hydrology and reservoir operations - Bin Yu; Yi Zheng; Shaokun He; Rui Xiong; Chao Wang (Journal of Hydrology, 2025)

Machine learning-assisted check dam planning on the Chinese Loess Plateau - Rui Fan; Nufang Fang; Yi Zeng; Renjie Zong; Qiong Wang; Yi Zhang; Zhihua Shi (Journal of Hydrology, 2025)

Screening and discovery of volatile allergenic components from artemisia ordosica in Yulin region of Northern China - Xiaoxue Mo; Cheng Wang; Yi Shan; Siqi Wang; Wen Yang; Zhaomin Xia; Zhanguo Qiao; Tao Zhang; Yuanyuan Ding; Rui Liu; Huaizhen He; Langchong He (Journal of Hazardous Materials, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

A method on the induction of piezoelectricity of PVDF by NaOH: Induced PVDF as ultrafiltration base membrane in interfacial polymerization to enhance the rejection of NaCl - Yuliang Chen; Wenmin Wang; Ying Liang; Chen Chen; Rui Meng; Libo Ba; Yuliang Wu; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi (Desalination, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Assessing CO2 storage mechanisms in marine shallow sediments to mitigate leakage risks from sub-seabed carbon storage: a numerical simulation study - Gang Hu; Xiangyi Yi; Xuanhua Tian; Rui Wang; Pengchun Li; Linxiong Peng; Xi Liang (Frontiers in Marine Science, 2025)
The geological storage of CO 2 in offshore saline aquifers has been implemented at various sites worldwide. While subsea sediments can serve as a critical barrier against potential leakage from deep storage formations, the mechanisms and storage capacity for CO 2 trapping within these sediments remain inadequately understood. This study developed a two-dimensional conceptual model of shallow sediments based on the Enping15–1 Carbon Capture and Storage (CCS) project site in the South China Sea. Furthermore, the CO 2 -water-rock reaction and storage mechanism were simulated using CMG-GEM, and the process of CO 2 leakage into the sediments was investigated. The results indicate that CO 2 leakage into the shallow seabed sediments is primarily sequestered through dissolution in pore water, accounting for 70% of the total sequestration, while residual and mineral trapping contribute 10–20%. The dissolution of CO 2 leads to pore water acidification, which triggers the dissolution of anorthite and K-feldspar under the prevailing initial geochemical conditions. Dynamic reaction behavior is mainly observed at the leading edge of the acidified plume. However, if the leakage rate exceeds a critical threshold, the advancing acidified plume front causes partial dissolution of previously precipitated carbonate minerals. The critical leakage rate is determined to be 0.2 m³/day for single-point leakage and 0.3 m³/day for multi-point leakage. Notably, multi-point, low-velocity leakage enhances secondary storage within the sediment, thereby reducing the risk of CO 2 release into the overlying seawater.

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

In vitro experiments and computer simulation techniques on the identification, screening and inhibition mechanism of xanthine oxidase (XO) inhibitory peptides from Esox lucius bone - Rui Geng; Yabo Wei; Yi Wang; Xin Guo; Xiaorong Deng; Lianfu Zhang; Jian Zhang (Food Bioscience, 2025)

Unveiling the potential supply of cultural ecosystem services on the Qinghai-Tibet Plateau: Insights from tourist hiking trajectories - Sheng Huang; Jiawei Yi; Yunyan Du; Fuyuan Liang; Rui Xu; Nan Wang; Jiale Qian; Wenna Tu; Peixian Luo; Andrew Z.F. Xing (Ecosystem Services, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Highly sensitive and wash-free human serum albumin detection based on filtration-to-enhancement compound microsphere system - Chen Yang; Xin Zhang; Minjing Mo; Guoqing He; Menglu Gao; Tao Jiang; Yihan Ma; Xiaotong Si; Rui You; Fubing Wang; Yi Yang (Chemical Engineering Journal, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

A new insight into the transformation mechanism between reactivity of aqueous monomer and chlorine resistance of polyester-amide nanofiltration membrane - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Yanshan Wang; Jun Cheng; Xuesong Yi; Heng Liang (Desalination, 2025)

Self-oxygenated biomimetic nano-heterojunction combats bacterial biofilm infections via near-infrared triggered ROS storms - Zhengcai Guo; Rui Zhang; Yi Li; Zhiling Chen; Tao Wang; Mingyu Wang; Xiaohong Wang; Yang Cao; Jinchun Tu; Delun Chen; Yang Wang; Qiang Wu (Chemical Engineering Journal, 2025)

Energy Release Efficiency and Mechanisms of Mining-Induced High-Energy Earthquakes in China - Zi-Bo Wang; Rui-Feng Liu; Ting-Ting Wang; Yi-Xiao Zhang; Xiao Ren (Rock Mechanics and Rock Engineering, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Potential of smartphone-based photogrammetry for measuring particle size and shape in field surveys - Pengju An; Rui Yong; Shigui Du; Yi Long; Jiannan Chen; Zhen Zhong; Kun Fang; Changshuo Wang; Jiamin Song (Bulletin of Engineering Geology and the Environment, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Iron-carbon amendment enhanced pollutant removal and greenhouse gas reduction in constructed wetlands under PFBA stress - Jiaqing Tao; Xiaoying Zheng; Chao Zhou; Zhilin Zhao; Tianxing Hu; Yi Fan; Yu Tang; Rui Wang; Tao Lin (Chemical Engineering Journal, 2025)

Atomically dispersed dual-active-site catalyst for enhanced oxygen reduction reaction: Synergistic effect of Fe and V in M−N−C structures - Qi-Dong Ruan; Rui Feng; Lu Liu; Lu Zhang; Jiu-Ju Feng; Yacheng Shi; Yi-Jing Gao; Ai-Jun Wang (Chemical Engineering Journal, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

The truncated AXIN1 isoform promotes hepatocellular carcinoma metastasis through SRSF9-mediated exon 9 skipping - Qian-qian Zhang; Ying-shuang Miao; Jun-yi Hu; Rui-xuan Liu; Yue-xiao Hu; Feng Wang (Molecular and Cellular Biochemistry, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Monitoring dust retention variations in different functional zones based on leaf magnetism and the influence of green belt spatial layouts on leaf dust retention - Ziwei Tao; Shuxuan Li; Bo Wang; Yi Xie; Rui Wang; Linglin Hu; Jia Jia; Junhui Zhang (Environmental Monitoring and Assessment, 2025)

BarH1 regulates the expression of conserved odorant-binding protein 22 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Ao Liu; Yi Wei; Rui-Lin Zhang; Hazem Abdelnabby; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Bacterial cellulose-based scaffold modified with anti-CD29 antibody to selectively capture urine-derived stem cells for bladder repair - Tianyi Shao; Mingzhe Yan; Rui Liu; Yanming Zhang; Banghui Wang; Yifei Li; Yuxin Liu; Danxia Li; Lixin Jin; Bingcheng Yi; Qihui Zhou (Carbohydrate Polymers, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Metabolome analysis reveals the involvement of oxylipins in regulating the maturation of conchosporangia in Pyropia haitanensis - Yi Liu; Haike Qian; Shanshan Zhu; Tingting Niu; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Algal Research, 2025)

Effects of ammonia nitrogen stress on liver tissue structure and physiological indicators, and metabolomic analysis of juvenile four-finger threadfin (Eleutheronema tetradactylum) - Jing-Hui Jin; Hao-Jie Wang; Eric Amenyogbe; Yi Lu; Rui-Tao Xie; Zhong-Liang Wang; Jian-Sheng Huang (Frontiers in Marine Science, 2025)
In intensive aquaculture, ammonia nitrogen (NH₃-N) is a major pollutant, causing oxidative stress and immune damage to aquatic organisms. The liver is crucial in protecting against biotic and abiotic stresses, but the response mechanisms to ammonia stress in juvenile four-finger threadfin ( Eleutheronema tetradactylum ) are not well understood. This study investigated these mechanisms by examining liver tissue structure, enzyme activities, and metabolomic changes in response to ammonia stress. Juvenile four-finger threadfin (7.4 ± 0.6 g) were divided into control, NH₃-N stress (50% LC 50 96 h , 10 ± 0.4 mg/L), and postexposure recovery groups. Stress durations of 12, 24, 48, and 96 h were evaluated, followed by 48 h recovery. Prolonged ammonia stress led to increased liver tissue damage, including disordered hepatocyte arrangement, swelling, necrosis, and the disappearance of nucleoli. After 48 h recovery, liver damage was alleviated but did not fully return to control levels, suggesting that the toxic effects of ammonia are recoverable yet persistent. Antioxidant enzyme activities (superoxide dismutase, catalase, and glutathione peroxidase) initially showed significant increases peaking at 24 h after stress, before declining by 96 h. Malondialdehyde levels rose initially and remained elevated compared with controls. After 48 h of recovery, antioxidant enzyme activity had not returned to control levels, indicating inadequate recovery from ROS-induced stress. Metabolomic analysis revealed 1219 significantly different metabolites in the 96 h stress group, with increases in L -histidine, L -threonine, and cholesterol. In the recovery group, 904 metabolites differed from controls, with notable reductions in urea and choline. The key affected pathways included amino acid, lipid, and nucleotide metabolism. This study elucidates the toxic effects of ammonia nitrogen on juvenile four-finger threadfin and their adaptive responses through physiological and metabolomic changes, providing insights for aquaculture practices and breeding ammonia-tolerant strains.

Effects of hypoxia on the heart of the juvenile four-finger threadfin (Eleutheronema tetradactylum) based on physiological indicators and transcriptome analysis - Yi Lu; Eric Amenyogbe; Ye- Yang; Zhong-liang Wang; Jing-hui Jin; Rui-tao Xie; Eric Kwabena Droepenu; Jian-sheng Huang (Frontiers in Marine Science, 2025)
This study evaluated the effects of hypoxia on the heart of juvenile four-finger threadfin ( Eleutheronema tetradactylum ) through physiological and transcriptome analysis. Juveniles with an average weight of 122.82 g and length of 24.60 cm were used. Hypoxia significantly increased serum myocardial enzyme activities, including creatine kinase (CK), creatine kinase-MB isoenzyme, lactate dehydrogenase (LDH), and α-hydroxybutyrate dehydrogenase (HDBH). These indicators initially rose and then declined, reflecting cardiac stress and suggesting their potential as early hypoxia biomarkers for real-time aquaculture monitoring. Histological analysis revealed structural damage in myocardial fibers under hypoxia, with increasing severity over time. This underscores the need to minimize oxygen fluctuations to prevent cardiac tissue degeneration. Transcriptome analysis identified upregulated genes involved in cell communication, immune responses, and intracellular signaling, offering potential targets for breeding hypoxia-tolerant species. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis highlighted key pathways such as mitogen-activated protein kinase (MAPK), hypoxia-inducible factor-1 (HIF-1), endocytosis, and phagosome formation. The MAPK pathway plays a critical role in cellular stress responses, including survival, proliferation, and apoptosis. Hypoxia-induced activation of MAPKs like ERK, JNK, and p38 regulates stress-responsive genes. HIF-1 signaling regulates oxygen homeostasis, with HIF-1α stabilizing hypoxia-responsive genes such as VEGFA, which promotes vascular remodeling and enhances oxygen delivery. These findings collectively offer practical applications for enhancing aquaculture management, such as monitoring biochemical markers, adopting hypoxia-tolerant breeding, and adjusting environmental conditions to mitigate stress, ensuring better productivity and sustainability. This research provides a foundation for further studies on the molecular mechanisms of hypoxia stress in aquaculture species.

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Chicken adipose tissue is differentially involved in primary and secondary regional immune response to NDV through miR-20a-5p-NR4A3 pathway - Yi Jiang; Rui Zhang; Xinxin Xu; Xiangnan Wang; Yufei Tian; Wei Zhang; Xiaoli Ma; Chaolai Man (Veterinary Immunology and Immunopathology, 2025)

Parametric investigation of suction actuators on the tunnel wall for alleviating pressure interactions in high-speed maglev train/tunnel system - Zheng-Wei Chen; Zhan-Hao Guo; Yi-Qing Ni; Zi-Jian Guo; Tian-Tian Wang; En-Ze Rui; Guang-Zhi Zeng (Tunnelling and Underground Space Technology, 2025)

Identifying publicly perceived high temperature thresholds across Chinese cities using geotagged social media data - Rui Xu; Jiawei Yi; Wei Qi; Yunyan Du; Sheng Huang; Nan Wang; Jiale Qian; Wenna Tu; Dingchen Hu; Ting Ma; Ashraf Dewan (Sustainable Cities and Society, 2025)

A Model for apparent permeability of organic slit nanopores in shale gas based on GCMC molecular simulation - Yi Zhang; Bin Zhang; Banghua Liu; Jie Liu; Qiansheng Wei; Hongjun Lu; Pengyu Zhu; Rui Wang; Yongli Yan (Fuel, 2025)

Bisphenol a monitoring by commercial pregnancy test strips transformed by DNA walking machine - Ziqiang Deng; Siyi Wang; Hongjie Song; Rui Liu; Yi Lv (Food Chemistry, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Efficient sustainable production of protocatechuic acid from glucose by engineered Bacillus licheniformis - Yi Rao; Jiaqi Wang; Rui Zhao; Yangyang Zhan; Xin Ma; Penghui He; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

Rheology, stability, and physicochemical properties of NaOH-tannic acid solvent for β-chitin dissolution - Shang-Ta Wang; Po-Jou Huang; Szu-Kai Chen; Chia-Rui Shen; Yi-Pin Chen; Min-Lang Tsai (Food Hydrocolloids, 2025)

Unsteady hydrate film controlled mechanism of rapid hydrate formation: From pilot to pore scales - Xuan Kou; Heng Zhang; Xiao-Sen Li; Kun Wan; Rui Xu; Yi Wang (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

A singular spectrum analysis-enhanced BiTCN-selfattention model for runoff prediction - Wen-chuan Wang; Feng-rui Ye; Yi-yang Wang; Miao Gu (Earth Science Informatics, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Construction risk probability assessment of shield tunneling projects in karst areas based on improved two-dimensional cloud model - Huaiyuan Sun; Yi Rui; Yanyun Lu; Yiming Dai; Xiang Wang; Xiaojun Li (Tunnelling and Underground Space Technology, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Recycled lithium battery nanomaterials as a sustainable nanofertilizer: Reduced peanut allergenicity and improved seed quality - Yaqi Jiang; Yi Sun; Pingfan Zhou; Guikai Zhu; Qibin Wang; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Science of The Total Environment, 2024)

Cyclic response and load transfer mechanism of suction bucket jackets supporting offshore wind turbines in soft clay - Baofeng Zhang; Rui Liu; Lizhong Wang; Xuetao Wang; Lilin Wang; Wei Li; Yi Hong (Ocean Engineering, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Room-temperature synthesis of carbon polymer dots from biomass for advanced sensing and fluorescent applications - Lin Lan; Rui Bao; Xin Kong; Liang Liu; Jinsong Wang; Jianhong Yi (Journal of Environmental Chemical Engineering, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

Antioxidant and anti-inflammatory activities and action mechanisms of exopolysaccharides from Lactiplantibacillus plantarum Z-1 - Qiong Xu; Miao-Miao Wang; Xinyue Li; Ya-Rui Ding; Xiao-Yi Wei; Tao Zhou (Food Bioscience, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

Feasibility of double nitrite supply through partial nitrification and partial denitrification driven by sludge fermentation - Jinjin Liu; Rui Wang; Shengjie Qiu; Yi Peng; Yongzhen Peng (Bioresource Technology, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

The fate of organic compounds in organic waste during torrefaction and implications for its valorization - Yi Hu; Rui Yang; Yiping Wu; Xuejiao Chen; Wei Lin; Hong Wang; Zhiyong Qi; Dongdong Zhang; Lin Ouyang (Environmental Pollution, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

MSC-mediated mitochondrial transfer restores mitochondrial DNA and function in neural progenitor cells of Leber’s hereditary optic neuropathy - Rui Wang; Feixiang Bao; Manjiao Lu; Xiaoyun Jia; Jiahui Xiao; Yi Wu; Qingjiong Zhang; Xingguo Liu (Science China Life Sciences, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects and fate of metal-based engineered nanomaterials in soil ecosystem: A review - Qibin WANG; Peng ZHANG; Weichen ZHAO; Shakoor NOMAN; Adeel MUHAMMAD; Guikai ZHU; Yi SUN; Quanlong WANG; Yaqi JIANG; Yukui RUI (Pedosphere, 2024)

An effective potential Bifidobacterium animalis F1-7 delivery strategy: Supramolecular hydrogel - sodium alginate/tryptophan-Sulfobutylether-β-cyclodextrin (Alg/Trp-SBE-β-CD) - Xiaoyang Huang; Jing Wang; Rui Liu; Chunrong Yang; Yanchun Shao; Xiaohong Wang; Huaxi Yi; Youyou Lu (Food Hydrocolloids, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

Hybrid plasma catalysis-thermal system for non-oxidative coupling of methane to ethylene and hydrogen - Rui Liu; Eduardo Morais; Dongxing Li; Pengfei Liu; Qian Chen; Shangkun Li; Li Wang; Xiaoxia Gao; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2024)

Cyclodextrin-based host-guest hierarchical fire retardants: Synthesis and novel strategy to endow polylactic acid fire retardancy and UV resistance - Jing Zhang; Xiuqin Zhang; Rui Wang; Wenqing Wang; Hui Zhao; Shuo Yang; Zhenfeng Dong; De-Yi Wang; Ye-Tang Pan (Carbohydrate Polymers, 2024)

Evolutionary dynamics of cooperation coupled with ecological feedback compensation - Zi-Xuan Guo; Tian-Jiao Feng; Yi Tao; Rui-Wu Wang; Xiu-Deng Zheng (BioSystems, 2024)

Associations between multiple urinary metals and metabolic syndrome: Exploring the mediating role of liver function in Chinese community-dwelling elderly - Yuqing Dai; Siyu Duan; Rui Wang; Pei He; Zhongyuan Zhang; Meiyan Li; Zhuoheng Shen; Yue Chen; Yi Zhao; Huifang Yang; Xiaoyu Li; Rui Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

The transcriptional changes of LrgA discriminates the responsiveness of Staphylococcus aureus towards blue light from that of photodynamic inactivation - Ruili Yang; Yi Xu; Jinchun Xu; Yali Li; Xiaoxiao Wan; Rui Kong; Chao Ding; Han Tao; Hui-Li Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Effects of ammonia nitrogen stress on the physiological, biochemical, and metabolic levels of the gill tissue of juvenile four-finger threadfin (Eleutheronema tetradactylum) - Jing-hui Jin; Eric Amenyogbe; Ye Yang; Zhong-liang Wang; Yi Lu; Rui-tao Xie; Eric Kwabena Droepenu; Jian-sheng Huang (Aquatic Toxicology, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Comparison of the Intestinal Microbiota Composition and Function of Red Claw Crayfish (Cherax quadricarinatus) Cultured in Ponds and Rice Fields - Libin Huang; Tianhe Lu; Xiaohua Lu; Jingu Shi; Yin Huang; Xuesong Du; Dapeng Wang; Yi Liang; Yanju Lei; Lianggang Wang; Rui Wang; Huizan Yang (Fishes, 2024)
The growth environment significantly influences the intestinal microbiota of aquatic organisms. We investigated the composition and functional differences in the intestinal microbiota of red claw crayfish (Cherax quadricarinatus) in rice fields (RB) and ponds (PB) by 16S rDNA high-throughput sequencing technology. The results indicate that the Shannon, Simpson, Sobs, Chao1, and ACE indices of PB are all higher than those of RB, demonstrating greater diversity and richness of intestinal microbiota. The dominant phyla in the intestinal microbiota of the Cherax quadricarinatus were Proteobacteria, Tenericutes, and Firmicutes. Tenericutes and Proteobacteria were significantly more abundant in the RB than in the PB, while Planctomycetes and Firmicutes were significantly more abundant in the PB than in the RB. The results of network correlation analysis indicate that Proteobacteria and Firmicutes exhibit strong connectivity with other microbial groups in the gut microbiota of Cherax quadricarinatus, showing significant centrality. They play an important role in the interactions within the gut microbiota community. The dominant bacterial genera in the Cherax quadricarinatus’s gut were Citrobacter, Candidatus_Bacilloplasma, and Clostridium_sensu_stricto_1. The abundance of the genus Clostridium was significantly higher in the PB than in the RB, whereas the abundance of Candidatus_Hepatoplasma and Vibrio was significantly lower in the PB than in the RB. The prediction function of KEGG enrichment showed that the abundance of Amino acid metabolism, Biosynthesis of Other Secondary Metabolites, Transport and Catabolism, Cancers, and Nervous System, Substance Dependence were significantly higher in the PB, while the infectious diseases pathway was enriched in the RB. In summary, our results revealed significant differences in the composition and diversity of intestinal microbiota in the Cherax quadricarinatus between rice paddy and pond farming environments. The intestinal microbiota of the Cherax quadricarinatus grown in pond environments exhibit higher diversity and stability, manifested by an increase in beneficial bacteria abundance and a decrease in opportunistic pathogens. These findings significantly improve understanding of the complex relationship among Cherax quadricarinatus, intestinal microbiota, and the environment.

Synergy of pollution reduction and carbon abatement of the 8 urban agglomerations in China: Status, dynamic evolution, and Spatial-temporal characteristics - Tiantian Yang; Lan Yi; Shuai Yan; Rui Zhang; Xiyu Wang (Resources Policy, 2024)

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Wastewater surveillance together with metaviromic data revealed the unusual resurgence of infectious diseases after the first wave of the COVID-19 outbreak - Ziqiang Zhang; Fenglan He; Liu Yi; Zhiqiang Deng; Rui Wang; Lixin Shen; Songzhe Fu (Journal of Hazardous Materials, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Multi-objective optimization driven by preponderant individuals and symmetric sampling for operational parameter design in aluminum electrolysis process - Lizhong Yao; Jia Chen; Ling Wang; Rui Li; Haijun Luo; Jun Yi (Swarm and Evolutionary Computation, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Critical factors in soil organic carbon mineralization induced by drying, wetting and wet-dry cycles in a typical watershed of Loess Plateau - Yi Zhang; Xiaojun Liu; Peng Li; Lie Xiao; Shixuan Zhou; Xing Wang; Rui Wang (Journal of Environmental Management, 2024)

Hydration properties and mesoscopic structures of different depolymerized konjac glucomannan: Experiments and molecular dynamics simulations - Yi Zhao; Juan Wang; Yuan Zhang; Rui He; Yuming Du; Geng Zhong (Food Hydrocolloids, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Climate and soil: Key Drivers of Plant Traits and Community Functional Differences in the Lakeshore Wetlands of Northern China - Rui Zhang; Zhichao Xu; Huamin Liu; Hongbo Yu; Feng Niu; Haitao Fang; Linqian Ma; Yunhao Wen; Lu Wen; Yi Zhuo; Lixin Wang (Wetlands, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

Age and dietary restriction modulate mitochondrial quality in quadriceps femoris muscle of male mice - Ting-Rui Zhang; Chun-Hsien Chiang; Tzu-Chieh Hsu; Chih-Yun Wang; Ching-Yi Chen (Biogerontology, 2024)

Investigation of the effects and mechanisms of manganese-based NMs on rice growth - Yaqi Jiang; Yi Sun; Peng Zhang; Pingfan Zhou; Qibin Wang; Guikai Zhu; Weichen Zhao; Yuanbo Li; Quanlong Wang; Yukui Rui (Environmental Science and Pollution Research, 2024)

Assessing ammonium pollution and mitigation measures through a modified watershed non-point source model - Feng Han; Qing Tian; Nengwang Chen; Zhaoping Hu; Yao Wang; Rui Xiong; Peng Xu; Wei Liu; Alejandra Stehr; Ricardo O. Barra; Yi Zheng (Water Research, 2024)

Early Cretaceous intrusive rocks in the Gangdese arc of southern Tibet do not support shallow subduction of the Neo-Tethyan oceanic lithosphere - Feng Wang; Qing Wang; Di-Cheng Zhu; Shi-Min Li; Peter A. Cawood; Rui-Qiang Wang; Jian-Kang Yi; Liang-Liang Zhang; Jin-Cheng Xie (Lithos, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Ru-Ni bimetallic catalyst supported on CeO2 boosts chemoselective methoxycarbonylation of olefins - Yi-Ran Du; Rui Wang; Qing-Shan Niu; Yi-Yu Tao; Bao-Hua Xu (Chemical Engineering Journal, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effects of belt trusses on drift control of frame-core tube structures - Wen-Bo Wang; Hong-Song Hu; Rui-Tao Wang; Yi-Chao Gao; Zi-Xiong Guo (Engineering Structures, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Effect of Rhodotorula mucilaginosa inoculation on the aroma development of a fermented vegetables simulated system - Rui Wang; Yi Zeng; Jiaqian Liang; Huixin Zhang; Junjie Yi; Zhijiia Liu (Food Research International, 2024)

Modeling of forced-vibration systems using continuous-time state-space neural network - Hong-Wei Li; Yi-Qing Ni; You-Wu Wang; Zheng-Wei Chen; En-Ze Rui; Zhao-Dong Xu (Engineering Structures, 2024)

Structural characterization and osteogenic differentiation-promoting activity of polysaccharide purified from Chroogomphus rutilus - Ying Zhou; Lanzhou Li; Zhen Sun; Rui Liu; Yanfeng Zhu; Jingzheng Yi; Yutong Li; Min Hu; Di Wang (Carbohydrate Polymers, 2024)

Serum Uric Acid Levels and Outcome of Acute Ischemic Stroke: a Dose–Response Meta-analysis - Peng Zhang; Rui Wang; Yang Qu; Zhen-Ni Guo; Qing Zhen; Yi Yang (Molecular Neurobiology, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Speed optimization for maximizing the ship’s economic benefits considering the Carbon Intensity Indicator (CII) - Rui Hua; Jingbo Yin; Shaohan Wang; Yi Han; Xinbo Wang (Ocean Engineering, 2024)

Regulating pathway for bacterial diversities toward improved ecological benefits of thiencarbazone-methyl·isoxaflutole application: A field experiment - Yonglu Wang; Liyun Zhang; Shumin Zhang; Shiliang Zhu; Fengsong Zhang; Guixiang Zhang; Bihua Duan; Rui Ren; Hongyu Zhang; Meng Han; Yi Xu; Yuyang Li (Journal of Environmental Management, 2024)

Hierarchical porous UiO-66 composites modified by dual competitive strategy for adsorption of oxytetracycline - Tao He; Yi Wang; Rui Han; Xiaodong Li; Shihai Cui; Jing Yang (Journal of Environmental Chemical Engineering, 2024)

Switchable circular polarized phosphorescence enabled by cholesteric assembled nanocelluloses - Xi Wang; Qing Miao; Wenjing Zhang; Yi Zhou; Rui Xiong; Yingying Duan; Xiao Meng; Chunhong Ye (Chemical Engineering Journal, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Kinetic modeling of cell growth and value-added products accumulation of Thraustochytrium striatum - Rui Xiao; Zhaohui An; Xiang Li; Zhi-Wu Wang; Yi Zheng (Biomass and Bioenergy, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Speciation analysis and toxicity evaluation of arsenolipids—an overview focusing on sea food - Caiyan Li; Jing Chen; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Sai-Yi Zhong (Archives of Toxicology, 2024)

Novel phenolic metabolites isolated from plant endophytic fungus Fusarium guttiforme - Jing-Yi Yue; Rui Wang; Tao Xu; Ju-Tao Wang; Yang Yu; Bai-Xiang Cai (Natural Product Research, 2024)

Mitigating cadmium accumulation in dicotyledonous vegetables by iron fertilizer through inhibiting Fe transporter IRT1-mediated Cd uptake - Zhong-Rui Xu; Ting-Ting You; Wen-Yi Liu; Kang Ye; Fang-Jie Zhao; Peng Wang (Chemosphere, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

RETRACTED: Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2024)

Fungus reduces tetracycline-resistant genes in manure treatment by predation of bacteria - Lei Liu; Qianxi Yin; Yu Hou; Rui Ma; Yi Li; Zhenyu Wang; Ganggang Yang; Yu Liu; Hailei Wang (Science of The Total Environment, 2024)

Evolution of Silurian phytogeography, with the first report of Aberlemnia (Rhyniopsida) from the Pridoli of West Junggar, Xinjiang, China - Bing-Cai Liu; Rui-Wen Zong; Kai Wang; Jiao Bai; Yi Wang; Hong-He Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Photocatalytic degradation of benzotriazole through synergy of electron donor–acceptor units and Au clusters in covalent organic frameworks - Hui Wang; Yuhan Xiong; Yi He; Lingru Kong; Lan Ding; Rui Wu; Xin-Lei Gao; Jie Ding; Nanqi Ren (Chemical Engineering Journal, 2024)

Square-wave alternating voltage driving promotes nanowire-assisted electroporation inactivation and fouling resistance of pathogenic bacteria for water disinfection - Ying-Wen Lu; Yang Wang; Yi-Rui Liu; Hai Liu (Chemical Engineering Journal, 2024)

Urea-boosted gas-exfoliation synthesis of lignin-derived porous carbon for zinc ion hybrid supercapacitors - Beichen Xue; Chaozhen Liu; Xiaofeng Wang; Yi Feng; Jiahuan Xu; Feng Gong; Rui Xiao (Chemical Engineering Journal, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

The combination of nanotechnology and potassium: applications in agriculture - Qibin Wang; Chen Shan; Peng Zhang; Weichen Zhao; Guikai Zhu; Yi Sun; Quanlong Wang; Yaqi Jiang; Noman Shakoor; Yukui Rui (Environmental Science and Pollution Research, 2023)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

Increased m6A-RNA methylation and demethylase FTO suppression is associated with silica-induced pulmonary inflammation and fibrosis - Yunyi Xu; Liqun Wang; Rui Qian; Manyu Zhao; Xuxi Chen; Donglei Sun; Ye Wang; Weibo Cheng; Yiping Chen; Qiurong He; Yi Dai; Yuqin Yao (Toxicology, 2023)

Effects of dry-salting and brine-pickling on physicochemical properties and flavor of spaghetti squash shreds - Yi Luo; Rui Wang; Hui Han; Shuo Wang; Jianxiang Ma; Chunlong Yuan; Yamei Ren (Food Bioscience, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Changes in Soil Bacterial and Fungal Community Composition and Response of Functional Groups to Different Proportions of N/P/K Fertilizer Short-Term Supply in Torreya grandis Soil - Chenliang Yu; Qi Wang; Congcong Kong; Yuanyuan Guan; Yi Li; Rui Zhang; Hua Qin; Jiasheng Wu (Journal of Soil Science and Plant Nutrition, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Prevalence of Ureaplasma species among patients at a tertiary hospital in China: a 10-year retrospective study from 2013 to 2022 - Ziran Wang; Mingqi Xia; Yu Chen; Zhuo Yang; Jie Yi; Lingjun Kong; Han Zhang; Guoju Luo; Rui Li; Yaling Dou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Engineering a Pseudomonas putida as living quorum quencher for biofilm formation inhibition, benzenes degradation, and environmental risk evaluation - Yi-Mei Xue; Yong-Chao Wang; Yu-Ting Lin; Guan-Yu Jiang; Rui Chen; Ruo-Lin Qin; Xiao-Qiang Jia; Can Wang (Water Research, 2023)

Recombinant Klotho alleviates vancomycin-induced acute kidney injury by upregulating anti-oxidative capacity via JAK2/STAT3/GPx3 axis - MengMeng Wang; Yue Zhou; GuoXiang Hao; Yue E. Wu; Rui Yin; Yi Zheng; Wei Zhao (Toxicology, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

DEMRL: Dynamic estimation meta reinforcement learning for path following on unseen unmanned surface vehicle - Kefan Jin; Hao Zhu; Rui Gao; Jian Wang; Hongdong Wang; Hong Yi; C.-J. Richard Shi (Ocean Engineering, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Macroscale insights into heterogeneous hydrate formation and decomposition behaviors in porous media - Xuan Kou; Xiao-Sen Li; Yi Wang; Rui Xu; Zhao-Yang Chen (Chemical Engineering Journal, 2023)

Rhizobia modulate the peanut rhizobacterial community and soil metabolites depending on nitrogen availability - Rui Wang; Bin Huo; La Chen; Keke Li; Ganfeng Yi; Entao Wang; Guohua Mi; Xinhua Sui (Biology and Fertility of Soils, 2023)

Neolignan derivatives from Penthorum chinense with antitumor activity in human colorectal cancer cells by regulating Wnt/β-catenin signaling pathway - Mengqi Lu; Jingya Ruan; Rui Yu; Ying Zhang; Wei Zhao; Dingshan Yang; Wanxia Wang; Yi Zhang; Tao Wang (Phytochemistry, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Nano-agriculture and nitrogen cycling: Opportunities and challenges for sustainable farming - Quanlong Wang; Li Gao; Yuanbo Li; Noman Shakoor; Yi Sun; Yaqi Jiang; Guikai Zhu; Fayuan Wang; Yunze Shen; Yukui Rui; Peng Zhang (Journal of Cleaner Production, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Spatiotemporal variations and dominated environmental parameters of nitrous oxide (N2O) concentrations from cascade reservoirs in southwest China - Chiquan He; Rui Qi; Haiyue Feng; Zhenzhen Zhao; Fushun Wang; Daoyuan Wang; Feifei Wang; Xueping Chen; Pu Zhang; Siliang Li; Yuanbi Yi (Environmental Science and Pollution Research, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Identification of priority pollutants and key factors affecting environmental risks of lead‑zinc mine tailing sites - Jing-yu Peng; Shuai Zhang; Yu-jing Wang; Rui-feng Zhao; Yi-ling Zhou; Jian-wei Zhou (Science of The Total Environment, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Contrasting the effect of aerosol properties on the planetary boundary layer height in Beijing and Nanjing - Xin Huang; Yuying Wang; Yi Shang; Xiaorui Song; Rui Zhang; Yuxiang Wang; Zhanqing Li; Yuanjian Yang (Atmospheric Environment, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Insights into the quantitative structure–activity relationship for ionic liquids: a bibliometric mapping analysis - Rui Huang; Hui Liu; Ze Wei; Yi Jiang; Kai Pan; Xin Wang; Jie Kong (Environmental Science and Pollution Research, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Insight into the structure–activity relationship in electrochromism of WO3 with rational internal cavities for broadband tunable smart windows - Xingrui Tong; Jinhui Wang; Ping Zhang; Pengyang Lei; Yi Gao; Ruirui Ren; Siyu Zhang; Rui Zhu; Guofa Cai (Chemical Engineering Journal, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Two Typical Synoptic-Scale Weather Patterns of Dust Events over the Tibetan Plateau - Xingya Feng; Rui Mao; Dao-Yi Gong; Guangjian Wu; Cuicui Shi; Guohao Liang; Yufei Wang (Asia-Pacific Journal of Atmospheric Sciences, 2023)

Iron-rich red mud and iron oxide-modified biochars: A comparative study on the removal of Cd(II) and influence of natural aging processes - Huabin Wang; Dingxiang Chen; Yi Wen; Yong Zhang; Ying Liu; Rui Xu (Chemosphere, 2023)

A method establishment and application for biofilm quorum quenching activity assay - Zhen Tong; Yong-Chao Wang; Guan-Yu Jiang; Xu-Rui Hu; Yi-Mei Xue; Can Wang (Chemosphere, 2023)

Lithium recovery and solvent reuse from electrolyte of spent lithium-ion battery - Rui Xu; Shuya Lei; Tianyu Wang; Chenxing Yi; Wei Sun; Yue Yang (Waste Management, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Elemental Geochemical Distribution of the Jurassic Yan'an Formation in the Ningdong Coalfield and its Controlling Effect on Coal Reservoir Properties - Jincheng Ye; Yafei Zhang; Wei He; Rui Tao; Shu Tao; Shida Chen; Yi Cui; Qi Wang (Natural Resources Research, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

A testis-specific gene doublesex is involved in spermatogenesis and early sex differentiation of the Chinese mitten crab Eriocheir sinensis - Long Wang; Zhi-Qiang Liu; Ke-Yi Ma; Jing-Rui Tao; Xiang Fang; Gao-Feng Qiu (Aquaculture, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Hybrid plasma-thermal system for methane conversion to ethylene and hydrogen - Rui Liu; Yingzi Hao; Tong Wang; Li Wang; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

A semi-analytical method for predicting train-induced vibrations considering train-track-soil and soil-pile-building dynamic interactions - Zi-Yu Tao; Chao Zou; Guang-Rui Yang; Yi-Min Wang (Soil Dynamics and Earthquake Engineering, 2023)

Immunotherapy in gastrointestinal cancers: advances, challenges, and countermeasures - Zi-Xian Wang; Yi-Qian Pan; Xuexin Li; Takeshi Tsubata; Rui-Hua Xu (Science Bulletin, 2023)

Preparation of high performance porous carbon by microwave synergistic nitrogen/phosphorus doping for efficient removal of Cu2+ via capacitive deionization - Huimin Huang; Yi Chen; Rui Ma; Juan Luo; Shichang Sun; Junhao Lin; Yanyi Wang (Environmental Research, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Assessment of dynamic digestion fate of soy protein gel induced by lactic acid bacteria: A protein digestomics research - Yaqiong Wang; Wenjing Sun; Yi Zhang; Wei Li; Qiuqin Zhang; Xin Rui (Food Hydrocolloids, 2023)

Exploring the heterogeneity in drivers of energy-saving behaviours among hotel guests: Insights from the theory of planned behaviour and personality profiles - Qian-Cheng Wang; Yi-Tian Ren; Xuan Liu; Rui-Dong Chang; Jian Zuo (Environmental Impact Assessment Review, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

The alteration of the expression level of neuropathy target esterase in human neuroblastoma SK-N-SH cells disrupts cellular phospholipids homeostasis - Wei-Yuan Hou; Xiaohua Song; Yuzhen Wang; Pingan Chang; Rui Chen; Yi-Jun Wu (Toxicology in Vitro, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Upregulation LncRNA MEG3 expression suppresses proliferation and metastasis in melanoma via miR-208/SOX4 - Yi Yang; Liang Jin; Juan He; Rui Wang; Yilin Wang; Jia Bai; Youbai Chen; Zhanpeng Luo (Molecular and Cellular Biochemistry, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

A stack-up electrochemical device based on metal-organic framework modified carbon paper for ultra-trace lead and cadmium ions detection - Yue-Hong Pang; Qiu-Yu Yang; Rui Jiang; Yi-Ying Wang; Xiao-Fang Shen (Food Chemistry, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Boosting elementary steps kinetics towards energetic alkaline hydrogen evolution via dual sites on phase-separated Ni–Cu–Mn/hydroxide - Zhimin Li; Sisi Xin; Yirong Zhang; Zhengfu Zhang; Chengping Li; Caiju Li; Rui Bao; Jianhong Yi; Mingli Xu; Jinsong Wang (Chemical Engineering Journal, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Root morphology and physiology responses of two subtropical tree species to NH4+-N and NO3−-N deposition in phosphorus-barren soil - Rui Zhang; Zhongyi Yang; Yunpeng Wang; Jiayi Wang; Yi Wang; Zhichun Zhou (New Forests, 2022)

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

New time-differenced carrier phase approach to GNSS/INS integration - Yi Mao; Rui Sun; Junhui Wang; Qi Cheng; Loo Chu Kiong; Washington Yotto Ochieng (GPS Solutions, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Mesoscale eddies induce variability in the sea surface temperature gradient in the Kuroshio Extension - Rui Tang; Yi Yu; Jingyuan Xi; Wentao Ma; Yuntao Wang (Frontiers in Marine Science, 2022)
The Kuroshio Extension (KE) region is one of the most energetic regions in the global ocean where prominent mesoscale dynamics persistently occur. The spatial distribution and temporal evolution of the sea surface temperature (SST) gradient and mesoscale eddies in the KE are investigated. The SST gradient can be applied for identifying the fronts, and the SST gradient within two times the radii of the eddies is composited to quantify the impact of eddies on frontal activities. Depressed SST gradients are identified for eddies with both polarities, but prominent spatial variance in the SST gradient reveals that a large SST gradient is located to the north of anticyclones and along the south periphery for cyclones. The eddies are further separated into two groups depending on their location relative to the main path of the KE, as the background fields to the north and south of the KE are largely different. The spatial pattern, e.g., monopole and dipole features, and temporal variation in the SST gradient are fully studied over the lifespans of eddies. The results show that most eddies can significantly weaken the internal SST gradient and induce the horizontal redistribution of the SST gradient in surrounding regions. Cyclonic eddies north of the KE elevate the fronts along the periphery of eddies. The temporal variability in the SST gradient is prominent and largely varies for each group of eddies. This study offers quantitative analyses of the spatial and temporal relationships between eddies and fronts that are important for understanding the mesoscale dynamics in the world’s oceans.

Investigation of present-day in situ stresses in a shale gas reservoir of Sichuan Basin, China: field measurement, stress field modeling, and engineering implications - Rui Yong; Jianfa Wu; Yi Song; Ersi Xu; Bin Xu; Quanzhou Wang; Lingke Wu (Arabian Journal of Geosciences, 2022)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Determination of the effective utilization coefficient of irrigation water based on geographically weighted regression - Rui Shi; Gaoxu Wang; Xuan Zhang; Yi Xu; Yongxiang Wu; Wei Wu (Frontiers of Earth Science, 2022)

Toxicities of nanomaterials and metals to rice under low atmospheric pressure - Kerui Guo; Dongheng Fu; Muhammed Adeel; Yunze Shen; Kexiang Wang; Yi Hao; Tonghao Bai; Yaoyao Wang; Yukui Rui (Acta Physiologiae Plantarum, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Chlorogenic acid, a natural product as potential inhibitor of COVID-19: virtual screening experiment based on network pharmacology and molecular docking - Wen-Xiang Wang; Ying-Rui Zhang; Shi-Ying Luo; Yun-Sen Zhang; Yi Zhang; Ce Tang (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

A new IMU-aided multiple GNSS fault detection and exclusion algorithm for integrated navigation in urban environments - Rui Sun; Junhui Wang; Qi Cheng; Yi Mao; Washington Yotto Ochieng (GPS Solutions, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Effect of different industrial activities on soil heavy metal pollution, ecological risk, and health risk - Zhijie Long; Yi Huang; Wei Zhang; Zhangliang Shi; Daming Yu; Ying Chen; Chao Liu; Rui Wang (Environmental Monitoring and Assessment, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Fabrication of Nanosuspensions to Improve the Oral Bioavailability of Total Flavones from Hippophae rhamnoides L. and their Comparison with an Inclusion Complex - Rui Tian; Hui Wang; Yi Xiao; Pengyue Hu; Ruofei Du; Xiufeng Shi; Zhengtao Wang; Yan Xie (AAPS PharmSciTech, 2020)

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

The impact of prenatal exposure to PM2.5 on childhood asthma and wheezing: a meta-analysis of observational studies - Wu Yan; Xu Wang; Tianyu Dong; Mengqi Sun; Mingzhi Zhang; Kacey Fang; Yi Chen; Rui Chen; Zhiwei Sun; Yankai Xia (Environmental Science and Pollution Research, 2020)

Transcriptional regulation of microRNA-126a by farnesoid X receptor in vitro and in vivo - Yi Yan; Shichao Wang; Rui Wang; Puxuan Jiang; Yaqing Chen; Liang Zhang; Chenjiao Hou; Lisheng Zhang (Biotechnology Letters, 2020)

Activation of Protein Kinase Cδ Contributes to the Induction of Src/EGF Receptor/ERK Signaling in Ammonia-treated Astrocytes - Guizhi Jia; Rui Wang; Yi Yue; Hongliang Dai (Journal of Molecular Neuroscience, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Detection performance of azimuthal electromagnetic logging while drilling tool in anisotropic media - Zhen-Guan Wu; Lei Wang; Yi-Ren Fan; Shao-Gui Deng; Rui Huang; Tao Xing (Applied Geophysics, 2020)

The bibliometric analysis and review of dioxin in waste incineration and steel sintering - Yi Xing; Hui Zhang; Wei Su; Qunhui Wang; Haibin Yu; Jiaqing Wang; Rui Li; Changqing Cai; Zhiliang Ma (Environmental Science and Pollution Research, 2019)

Re-examining the role of ventral tegmental area dopaminergic neurons in motor activity and reinforcement by chemogenetic and optogenetic manipulation in mice - Man-Yi Jing; Xiao Han; Tai-Yun Zhao; Zhi-Yuan Wang; Guan-Yi Lu; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Seedling growth and nutrition responses of two subtropical tree species to NH4+-N and NO3−-N deposition - Rui Zhang; Zhichun Zhou; Yi Wang; Guoqing Jin (New Forests, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Study on the denitrification performance of FexLayOz/activated coke for NH3-SCR and the effect of CO escaped from activated coke at mid-high temperature on catalytic activity - Jiaqing Wang; Pei Lu; Wei Su; Yi Xing; Rui Li; Yuran Li; Tingyu Zhu; Huifang Yue; Yongkang Cui (Environmental Science and Pollution Research, 2019)

Simultaneous removal of NOx and Hg0 from simulated flue gas over CuaCebZrcO3/r-Al2O3 catalysts at low temperatures: performance, characterization, and mechanism - Huifang Yue; Pei Lu; Wei Su; Yi Xing; Rui Li; Jiaqing Wang (Environmental Science and Pollution Research, 2019)

Characterization and phylogenetic analysis of the complete maternal mitochondrial genome of freshwater mussel Aculamprotula scripta (Bivalvia: Unionidae: Unioninae) - Rui-Wen Wu; Sa Wang; Yi-Tong Liu; Xiong-Jun Liu; Chun-Hua Zhou; Shan Ouyang; Xiao-Ping Wu (Conservation Genetics Resources, 2018)

Morphology and molecular phylogeny of two new species of Spirostrombidium (Ciliophora, Oligotrichia), with a key to the species of Spirostrombidium - Rui Wang; Wen Song; Zhenzhen Yi; Khaled A. S. Al-Rasheid; Xiaozhong Hu (Systematics and Biodiversity, 2018)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Low dosage of arsenic trioxide (As2O3) inhibits angiogenesis in epithelial ovarian cancer without cell apoptosis - Dehong Luo; Xiaoyuan Zhang; Renle Du; Wenjuan Gao; Na Luo; Shuangtao Zhao; Yi Li; Rui Chen; Hui Wang; Yonghua Bao; Wancai Yang; Daishun Liu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Transformations of 2-line ferrihydrite and its effect on cadmium adsorption - Yi Huang; Shipeng Zhang; Chao Liu; Huilin Lu; Shijun Ni; Xin Cheng; Zhijie Long; Rui Wang (Environmental Science and Pollution Research, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Spatial distribution of soil cadmium and its influencing factors in peri-urban farmland: a case study in the Jingyang District, Sichuan, China - Bing Li; Rui Xiao; Changquan Wang; Linhai Cao; Yi Zhang; Shunqiang Zheng; Lan Yang; Yong Guo (Environmental Monitoring and Assessment, 2017)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Exogenous Abscisic Acid Alleviates Cadmium Toxicity by Restricting Cd2+ Influx in Populus euphratica Cells - Yansha Han; Shaojie Wang; Nan Zhao; Shurong Deng; Chenjing Zhao; Nianfei Li; Jian Sun; Rui Zhao; Huilan Yi; Xin Shen; Shaoliang Chen (Journal of Plant Growth Regulation, 2016)

Anomalous astronomical time-latitude residuals: a potential earthquake precursor - Hui Hu; You-Jin Su; Yi-Fei Gao; Rui Wang (Applied Geophysics, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Current approaches to reduce or eliminate mitochondrial DNA mutations - Liang Yang; Tingfang Mei; Xiaobing Lin; Haite Tang; Yi Wu; Rui Wang; Jinglei Liu; Zahir Shah; Xingguo Liu (Science China Life Sciences, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Candidate gene prediction via quantitative trait locus analysis of fruit shape index traits in apple - Ke Cao; Yuansheng Chang; Rui Sun; Fei Shen; Ting Wu; Yi Wang; Xinzhong Zhang; Zhenhai Han (Euphytica, 2015)

Tempo-spatial analysis of water quality in tributary bays of the Three Gorges Reservoir region (China) - Jialiang Tang; Tao Wang; Bo Zhu; Pei Zhao; Yi Xiao; Rui Wang (Environmental Science and Pollution Research, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Erratum to: Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

Tumor Necrosis Factor-Related Apoptosis Inducing Ligand Gene Polymorphisms are Correlated with Gastric Cancer in Central China - Changgao Wang; Shufang Xu; Fengming Yi; Xiaobing Wang; Yuan Lei; Sha Huang; Rui Zhou; Bing Xia (Pharmaceutical Research, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

The Influence of Land Use on the Abundance and Diversity of Ammonia Oxidizers - Dayong Zhao; Juan Luo; Jianqun Wang; Rui Huang; Kun Guo; Yi Li; Qinglong L. Wu (Current Microbiology, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

3-D observations of a red tide event in the offshore water along the western Guangdong coast - Lingling Xie; Qingxiang Chen; Jianyu Hu; Shuwen Zhang; Xiaofei Yi; Fajin Chen; Rui Deng; Xiaodong Deng; Jing Wang; Yiquan Qi (Acta Oceanologica Sinica, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Association of microRNA-3144 variant with the susceptibility to hepatocellular carcinoma - Jun Zhang; Rui Wang; Min Cai; Shunji Yu; Yanyun Ma; Weihong Xu; Chunfang Gao; Jiucun Wang; Lifang Hou; Yi Liu; Jie Liu (Genes & Genomics, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Effects of nitrogen deposition on growth and phosphate efficiency of Schima superba of different provenances grown in phosphorus-barren soil - Rui Zhang; ZhiChun Zhou; WenJian Luo; Yi Wang; ZhongPing Feng (Plant and Soil, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Genome-wide identification and transcription analysis of soybean carotenoid oxygenase genes during abiotic stress treatments - Rui-Kai Wang; Chun-E Wang; Yun-Yan Fei; Jun-Yi Gai; Tuan-Jie Zhao (Molecular Biology Reports, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

Chaiqin Chengqi Decoction decreases IL-6 levels in patients with acute pancreatitis - Ling Wang; Yuan Li; Qin Ma; Yong Liu; Yuan-yi Rui; Ping Xue; Zong-guang Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Innate and evolutionarily increased advantages of invasive Eupatorium adenophorum over native E. japonicum under ambient and doubled atmospheric CO2 concentrations - Yan Bao Lei; Yu Long Feng; Yu Long Zheng; Rui Fang Wang; He De Gong; Yi Ping Zhang (Biological Invasions, 2011)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

Localized Delivery of Antisense Oligonucleotides by Cationic Hydrogel Suppresses TNF-α Expression and Endotoxin-Induced Osteolysis - Lei Dong; Zhen Huang; Xing Cai; Jiawei Xiang; Yi-An Zhu; Rui Wang; Jiangning Chen; Junfeng Zhang (Pharmaceutical Research, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Regulation of β cleavage of amyloid precursor protein - Jun-Feng Wang; Rui Lu; Yi-Zheng Wang (Neuroscience Bulletin, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Radiosonde observations of high-latitude planetary waves in the lower atmosphere - Rui Wang; ShaoDong Zhang; Fan Yi (Science China Earth Sciences, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Mechanism of action of two insect toxins huwentoxin-III and hainantoxin-VI on voltage-gated sodium channels - Rui-lan Wang; Su Yi; Song-ping Liang (Journal of Zhejiang University-SCIENCE B, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Removal of Benzo[a]pyrene by a fungus Aspergillus sp. BAP14 - Yi-Rui Wu; Teng-Teng He; Jing-Sheng Lun; Khalid Maskaoui; Tong-Wang Huang; Zhong Hu (World Journal of Microbiology and Biotechnology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Preparation and bioevaluation of 99mTc-HYNIC-annexin B1 as a novel radioligand for apoptosis imaging - Quan-Yong Luo; Fang Wang; Zhi-Yong Zhang; Yi Zhang; Han-Kui Lu; Shu-Han Sun; Rui-Sen Zhu (Apoptosis, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Potency of some novel insecticides at various environmental temperatures onMyzus persicae - Xiao-yi Wang; Zuo-rui Shen (Phytoparasitica, 2007)

Transgenic Mice Can Express Mutant Human Coagulation Factor IX with Higher Level of Clotting Activity - Jing-Bin Yan; Shu Wang; Wen-Ying Huang; Yan-Ping Xiao; Zhao-Rui Ren; Shu-Zheng Huang; Yi-Tao Zeng (Biochemical Genetics, 2006)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

Changes of Bt Toxin in the Rhizosphere of Transgenic Bt Cotton and its Influence on Soil Functional Bacteria - Yu-Kui Rui; Guo-Xiang Yi; Jing Zhao; Bao-Min Wang; Zhao-Hu Li; Zhi-Xi Zhai; Zhong-Pei He; Qing X. Li (World Journal of Microbiology and Biotechnology, 2005)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Polymorphism of the mouse gene for the interleukin 10 receptor alpha chain (Il10ra) and its association with the autoimmune phenotype - Zan-Mei Qi; Jun Wang; Zheng-Rong Sun; Feng-Mao Ma; Qing-Rui Zhang; Sachiko Hirose; Yi Jiang (Immunogenetics, 2005)

Streptozotocin-induced diabetes impairs G-protein linked signal transduction in vascular smooth muscle - Shehla Hashim; Yi Yong Liu; Rui Wang; Madhu B. Anand-Srivastava (Molecular and Cellular Biochemistry, 2002)

Volatile Compounds in Anal Gland of Siberian Weasels (Mustela sibirica) and Steppe Polecats (M. eversmanni) - Jian-Xu Zhang; Lixing Sun; Zhi-Bin Zhang; Zu-Wang Wang; Yi Chen; Rui Wang (Journal of Chemical Ecology, 2002)